Nunamii’luni quvianaqtuq (It is a happy moment to be on the land): Feelings, freedom and the spatial political ontology of well-being in Gjoa Haven and Tikiranajuk, Nunavut - Robertson, S. (Sean); Ljubicic, G. (Gita) (Environment and Planning D: Society and Space, 2019)
In Uqsuqtuuq (Gjoa Haven, Nunavut), we worked with Uqsuqtuurmiut (people of Uqsuqtuuq) on local priorities of caribou and well-being. We learned about the importance of relationality. In order to follow relations and their effects, we draw upon health geography concepts: therapeutic landscape and environmental dispossession. As therapeutic techniques, Uqsuqtuurmiut practice their knowledge and norms with people; animals; and the land, water and sea ice towards physical and emotional gains. They also make health discourses that can be beneficial. The social aspects of this environmental investment move beyond the individuation found in the hamlet to produce a sense of unity (or freedom) with emotional benefit. It was ultimately expressed as the happiness inherent to being ‘on the land’ and well-being. Moreover, we draw on relational materialism to illustrate not only a holistic form of well-being, but also how Uqsuqtuurmiut self-landscape encounters involve the spatialization of ontological difference. To better appreciate how this therapeutic worlding experience provides emotional gains related to self-determination, we reframe freedom from simply being the erasure of interpersonal borders to also include a sense of interdependence and collective autonomy. We further explain happiness as the therapeutic benefit of an Uqsuqtuurmiut spatial political ontology.